Severe complicated shigellosis case developed by young pregnant woman - E. A. Kozhukhova; I. L. Kozhevnikova; S. L. Nikolaenko; V. D. Ivaschenko (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова, 2021)
No doubts that shigellosis severity directly depends on the spread of the gut specific lesion. There are some data published on the basis of autopsy records and pointing to shigella caused lesion spreading both to colon and ileum in adult cases especially in those older than 60 y.o. or with any immunosuppressive premorbid background. Obviously, the gut mucosa condition determines the local resistance potential and moreover it's shown that in shigellosis cases, the histologic pattern of gut mucosa depends on quantity and quality of neutrophils, extremely important to control the intensity of agent invasion. Viral infections with concomitant neutropenia are commonly considered as immune suppressive conditions. As to Herpes virus infection, it's well known as the large mucosa lesion disease that can subsequently lead to aggravation of any forthcoming acute bacterial infection. The paper suggests the description of shigellosis case confirmed with the use of PCR test (PCR kit Amplisens All-bacto-screen-FL Lab, Interlabservice) and developed by young woman with unfavorable premorbid condition. The disease course turned to be severe and complicated by the peritonitis development. The aggravating factors in the proposed case were likely such immune modulating concurrent conditions as Herpes virus infection and pregnancy. The clinical example demonstrates that young people can develop severe complicated shigellosis course given burdened premorbid background availability.